Development of maintenance record database using GIS technique: a case study bridge Kuantan - Nor Hafipah, Mohamed Dasuki (2013)
Conventional database management systems bridge maintenance have many limitations in recording the bridge components, maintenance of historical data, geographical information about the bridge, and storage of information related images. Geographical Information System (GIS) has capability to record geographical data objects and associated characteristic. The system is also capable of managing, analyzing, and displaying all forms of geographic data objects and their properties. The main objective of this study is to develop a prototype system using the bridge maintenance database using Geographical Information System techniques. Data on components, bridge maintenance records obtained from the Department of Public Works District of Kuantan. Location and photos related bridges determined and recorded. Bridge maintenance records database was developed using GIS techniques. This prototype gives ideas to the relevant authorities and makes it as a starting point in developing its bridge maintenance database more effectively.